XRecursive, An Efficient Relational Method to Store XML Data - Jasni, Mohamad Zain; K.F., Rabbi; M.A., Ibrahim Fakharaldien; Norrozila, Sulaiman (2011)
Storing XML documents in a relational database is a promising solution because relational databases are mature and scale very well and they have the advantages that in a relational database XML data and structured data can coexist making it possible to build application that involve both kinds of data with little extra effort . In this paper, we propose an algorithm schema named XRecursive that translates XML documents to relational database according to the proposed storing structure. The steps and algorithm are given in details to describe how to use the storing structure to storage and query XML documents in relational database. Then we report our experimental results on a real database to show the performance of our method in some features.